HLY1104 Winter Cruise Chlorophyll - Dean Stockwell; Carin Ashjian; Robert Campbell; Stephen Okkonen (Arctic Data Center, 2014)
Chlorophyll data collected during the USCGC Healy cruise to the Chukchi, Beaufort, and Bering Seas in Nov. - Dec. 2011. See Readme file for methods.